Analysis Of Handling Incoming Letters To The Simple Electronic Agenda Book System Of Pt. Angkasa Pura I - Tsany, Raihan; Marsofiyati; Kurnianti, Destria (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research was conducted at PT Angkasa Pura I with the aim of knowing the handling of incoming letters in a simple electronic agenda book system. Data for this research was obtained through several methods, namely observation, interviews and documentation. The analysis of this research was prepared using descriptive analysis methods to provide a comprehensive picture of the handling of incoming mail. The descriptive method is used to describe what exists in a systematic, factual and accurate manner regarding the facts being investigated. Therefore, it is hoped that this research can provide in-depth insight into the effectiveness and efficiency of handling incoming letters in a simple electronic agenda book system at PT Angkasa Pura I. Keywords: Incoming Latter, Receipt of Incoming Mail, Correspondence.